THE MECHANISM OF AURICULOTHERAPY: A CASE REPORT BASED ON THE FRACTAL STRUCTURE OF MERIDIAN SYSTEM - Bernardo-Filho, Mario; de Sá-Caputo, Danúbia da Cunha; Marin, Pedro J; Chang, Shyang (African journal of traditional, complementary, and alternative medicines, 2014)
Background: Chinese meridian system of acupuncture has recently been deciphered as the fractal continuum of neurovascular bundles and its smaller branches. The corresponding acupuncture mechanism of therapeutics has been attributed to the magneto-electric inductive effects of the meridian system via chaotic wave of nerve innervations and blood flow. Hence, based on the proposed theory, the important sensory organ of the ears should be able to exert its influence on visceral organs and peripheral limbs. This investigation aims to verify if such a possible correlation exists between an external region of the ear and the muscle of biceps brachii in the French auriculotherapy. Materials and Methods: A region between the points of elbow and shoulder in the scaphoid fossa (upper arm), was chosen. Before the recording of surface electromyograms (EMGs), of the muscle of biceps brachii, two subjects were asked to carry out maximum voluntary isometric contractions (MVICs), of the arm. In addition, the same volunteers would be served as control group. Consequently, each subject was required to perform the three treatments of control, sham, and acupressure in random order. EMG signals were recorded for later analysis. Results: Results indicate that the acupressure with finger at a specific point which bears possibly with a somatopic relation to the biceps brachii muscle can, in a man, modify the response of the EMGs associated with the corresponding muscle while the response of the acupressure of a sham point has different responses. Moreover, the MVIC parameters were higher in acupressure treatment than those of control and sham treatments for both subjects. Conclusion: In conclusion, the analysis of the findings permits us to speculate that the stimulation with the fingers in the scaphoid fossa of the ear presents electromyographic responses related to the biceps brachii muscle. Hence, the mechanism of French auriculotherapy could be derived from the same principle as that of the Chinese acupuncture.